Descriptive Analysis of Physical Activity Initiatives for Health Promotion in Saudi Arabia - Hazzaa M. Al-Hazzaa; Mezna A. AlMarzooqi (Frontiers Media S.A., 2018)
Background: Although the benefits of physical activity are well acknowledged, a high percentage of Saudi population, especially females, remain essentially physically inactive. Getting inactive people to start participating in physical activity and to keep exercising remains a great challenge. Physical activity initiatives in the country have not been previously documented. Therefore, the aim of this article was to provide a narrative review of the physical activity initiatives and discusses influencing factors.Methods: Publically-available physical activity initiatives conducted before June 2018 were searched through the web or they were obtained straight from the organization themselves. The search focus was on any initiative aimed to promote physical activity and mass sports participation and encourage people to adopt active living habit.Results: Numerous initiatives aimed at promoting physical activity existed in Saudi Arabia. However, a common attribute of these initiatives is that they were fragmented, short term attempts, and lacked a coordinating body. The majority of the physical activity initiatives also lacked objective evaluations of their outcomes. It was clear that more physical activity opportunity must be provided for Saudi girls, women, and elderly. There is a need for establishing a national policy encouraging active living and discouraging sedentary lifestyle with contributions from all involved parties.Conclusions: Based on the available evidences, more intensified efforts toward promoting physical activity and reducing sedentary behaviors among Saudi population are needed in order to reduce the risks of NCD's.